2007
DOI: 10.1113/jphysiol.2007.138776
|View full text |Cite
|
Sign up to set email alerts
|

Multiphoton imaging of chick retinal development in relation to gap junctional communication

Abstract: Neural progenitor cells in the developing retina extend processes that stretch from the basal vitread surface to the apical ventricular surface. During the cell cycle, the nucleus undergoes interkinetic nuclear migration (INM), moving in a vitread direction during G1, passing through S-phase at its peak and then, on entering G2, returning towards the ventricular surface where it enters M-phase and divides. We have previously shown that individual saltatory movements of the nucleus correlate with transient chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
(25 reference statements)
1
5
0
Order By: Relevance
“…Pearson et al [50]. Using a modified experimental system, it was shown that gap-junctional communication is important for the ability of progenitor cells and newborn neurons to change the direction of their movement [51]. In the case of the zebrafish retina, genetic tools can be combined with liveimaging methods.…”
Section: Retinamentioning
confidence: 99%
“…Pearson et al [50]. Using a modified experimental system, it was shown that gap-junctional communication is important for the ability of progenitor cells and newborn neurons to change the direction of their movement [51]. In the case of the zebrafish retina, genetic tools can be combined with liveimaging methods.…”
Section: Retinamentioning
confidence: 99%
“…The movement of Cx43 puncta in the cell body shows strong correlation with the nuclear translocation, implying the association with the centrosome and a potential role of Cx43 in nuclear translocation. This is coincident with the involvement of Cx43 in the interkinetic nuclear migration in chick retina development (Becker, D. 2007). The above studies on neuronal migration seem to support a role of Cx43 in the locomotion machinery of the neurons.…”
Section: Cell Migration Is a Common Phenomenon During Development Andsupporting
confidence: 73%
“…Furthermore the results with HeLa cells show that the activation of apoptotic reactions is not a non specific effect of ODQ Evidence has accum gulates highly complex cellular functions. It was shown that a reduction of gap junction coupling reduced the differentiation of cultured chick leg bud mesenchymal cells [27], the proliferation and fusion of the myoblast [6,7] and the differentiation of progenitor cells of the retina [28,29]. Additionally, it was observed that inhibition of gap junction coupling was involved in stimulation of apoptosis in granulosa cells [10,20].…”
Section: Discussionmentioning
confidence: 99%